Essays on stock market volatility and market efficiency in Islamic countries and developed non-Islamic countries - Vu, Thi Hong Nhung (2020)
Stock market volatility is the common concern of investors and regulators. Stock prices are expected to volatile in nature and hence they exhibit some degree of volatility. The literature suggests that the stock prices vary too much to be explained by fundamental values which contradicts to the idea of the Efficient Market Hypothesis. The recent trend on studying volatility and market efficiency has considered non-financial factors. One of them is religion. Among the popular religions, Islam is the fastest growing religion in terms of population. The argument of the impact of religion on stock market volatility and market efficiency is still controversial. Hence, this thesis aims to investigate this impact by comparing the stock markets in Islamic countries and non-Islamic developed countries with the focus on stock market volatility, excess volatility and market efficiency. The results show that Islam and volatility are related and such relationship is stronger in Islamic countries than in developed countries and the strength and sign of the relationship change after political and economic crisis. It supports the finding that Islamic countries’ stock markets are excessively volatile in the long-term while excess volatility is absent in stock markets in developed countries. Therefore, there is no surprise when developed countries’ markets are found to be more efficient than Islamic countries’ markets. However, weak-form efficiency is rejected in stock markets in not only Islamic and but also developed countries. Moreover, we find the evidence of the improvement in efficiency overtime in Islamic countries’ markets. Besides, countries with similar market capitalisation do not have similar degree of market efficiency. The findings in this thesis suggest that Islamic countries can benefit from portfolio diversification and improved regulations and policies.